SPECT imaging of 226Ac as a theranostic isotope for 225Ac radiopharmaceutical development. (21st September 2022) - Koniar, Helena; Rodríguez-Rodríguez, Cristina; Radchenko, Valery; Yang, Hua; Kunz, Peter; Rahmim, Arman; Uribe, Carlos; Schaffer, Paul
Abstract: Objective . The development of alpha-emitting radiopharmaceuticals using 225 Ac ( t ½ = 9.92 d) benefits from the quantitative determination of its biodistribution and is not always easy to directly measure. An element-equivalent matched-pair would allow for more accurate biodistribution and dosimetry estimates. 226 Ac ( t ½ = 29.4 h) is a candidate isotope for in vivo imaging of preclinical 225 Ac radiopharmaceuticals, given its 158 keV and 230 keV gamma emissions making it suitable for quantitative SPECT imaging. This work aimed to conduct a performance assessment for 226 Ac imaging and presents the first-ever 226 Ac SPECT images. Approach . To establish imaging performance with regards to contrast and noise, image quality phantoms were scanned using a microSPECT/CT system. To assess the resolution, a hot rod phantom with cylindrical rods with diameters between 0.85 and 1.70 mm was additionally imaged. Two collimators were evaluated: a high-energy ultra-high resolution (HEUHR) collimator and an extra ultra-high sensitivity (UHS) collimator. Images were reconstructed from two distinct photopeaks at 158 keV and 230 keV. Main results . The HEUHR SPECT image measurements of high activity concentration regions were consistent with values determined independently via gamma spectroscopy, within 9% error. The lower energy 158 keV photopeak images demonstrated slightly better contrast recovery. In the resolution phantom, the UHS collimator only resolved rods ≥1.30 mm and ≥1.50 mm for the 158 keV and 230 keV photopeaks, respectively, while the HEUHR collimator clearly resolved all rods, with resolution <0.85 mm. Significance . Overall, the feasibility of preclinical imaging with 226 Ac was demonstrated with quantitative SPECT imaging achieved for both its 158 keV and 230 keV photopeaks. The HEUHR collimator is recommended for imaging 226 Ac activity distributions in small animals due to its resolution <0.85 mm. Future work will explore the feasibility of using 226 Ac both as an element-equivalent isotope for 225 Ac radiopharmaceuticals, or as a standalone therapeutic isotope.